Platelet Aggregation and Platelet Factor 3 Activity in Myeloproliferative Disorders - Tangün, Y (Thrombosis and Haemostasis, 1971)
33 patients with myeloproliferative disorder were studied and in 28 (84%) various anomalies of platelet function were observed. Single, or more commonly, multiple platelet aggregation defects and impaired release of platelet ADP and platelet factor 3 activity were the chief anomalies noted, whether thrombocytosis was present or not. The effect of myelosuppressive therapy upon the defects demonstrated varied from patient to patient, and from one anomaly to another. Reducing the high platelet count to normal levels does not seem to be sufficient to eradicate qualitative platelet defects.